Kelas Sosial dan Akses terhadap Keadilan: Kajian Ketimpangan dalam Penegakan Hukum di Indonesia : Penelitian - Sri Damayanti; Fauzan Rasyid Adhari; Januar Alpahluzie; Fitra Fajar Ananta (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the forms of social inequality in law enforcement in Indonesia and how economic, power, educational, and gender factors influence access to justice. The phenomenon of legal inequality indicates that the Indonesian legal system has not fully implemented the principle of equality before the law. This study uses a descriptive qualitative method with a library research approach. Data were collected through analysis of various secondary sources such as scientific journals. The results show that inequality in law enforcement is still influenced by economic factors, where the poor have difficulty obtaining adequate legal assistance, while influential groups have the financial capacity to influence the legal process. In addition, low legal literacy, geographical inequality, and gender bias also exacerbate inequality in the legal system. Discriminatory practices by law enforcement officers against lower-class communities also weaken public trust in legal institutions. This study emphasizes the importance of structural reform in the legal system so that justice can be accessed equally regardless of social class.